The Association Between ABO Blood Groups and Adenomyosis - Pun, Sunita; Ojha, Neebha; Koirala, Poonam (Journal of Nepal Health Research Council, 2025)
Background: Several studies have investigated the relationships between female reproductive diseases and ABO blood groups. However, evidence regarding the potential association between ABO blood groups and adenomyosis remains limited. The aim of the study, thus, was to investigate the association between ABO blood groups and the risk of developing adenomyosis in Nepalese women.Methods: A cross-sectional study was conducted at the department of obstetrics and gynecology, Tribhuvan University Teaching Hospital, Maharajgunj, from 2016 to 2017. Statistical analysis was done using Statistical Package for Social Sciences (SPSS, 29). Odd ratio with their corresponding 95% confidence intervals, and P-value were calculated and analyzed. A P-value equal or < 0.05 was considered statistically significant. Results: A total of 249 with recorded ABO groups were included in this study. Of these, 85 cases (34%) were histologically confirmed to have adenomyosis. The most frequent ABO blood group was B (43%), while the least frequent group was AB (6%). Women with blood group B had a significantly increased risk of developing adenomyosis, with an odds ratio of 2.3 (95% CI: 1.22-4.43, P value = 0.01). Conversely, blood group A was associated with a significantly reduced risk of adenomyosis, with an odds ratio of 0.41 (95% CI: 0.19-0.89, P value= 0.03).      Conclusions: This study demonstrated that women with blood group B have a 2.3-fold higher risk of developing adenomyosis, whereas those with blood group A may have a protective effect. Multicenter studies with larger sample sizes and diverse demographics groups are needed to substantiate these findings.Key Words: Adenomyosis; ABO blood group; risk factors.